Estudo comparativo do desempenho de rebolos com grãos superabrasivos e convencionais - Bianchi, Eduardo Carlos [UNESP]; Monici, Rodrigo Daun [UNESP]; Da Silva, Eraldo Jannone [UNESP]; De Aguiar, Paulo Roberto [UNESP] (My University, 2001)
Grinding is a precision machining process which is widely used in the manufacture of components requiring fine tolerances and smooth surfaces. There are several imput parameters (cutting conditions, cutting fluid and grinding wheel type used, dressing conditions etc.) which can affect the process variables (tangential and normal cutting forces, roughness, grinding temperatures, G ratio, etc.) leading to differences in the roughness, in the surface integrity and in the mechanical strength of the ground component. Consequently, the imput parameters must be controlled in order to insure the workpiece final quality. This paper presents a comparative evaluation of the performance of two types of grinding wheels [a conventional (Al2O3) and a superabrasive (CBN)] when grinding a VC131 steel, by the analysis of specific process variables when varying the cutting conditions. Highest values of G ratio and lowest workpiece roughness was observed when using CBN grinding wheels. This confirms the global trend of replacement of alumina grinding wheels by CBN, when grinding DTG (difficult to grind) materials.
Comparative evaluation of the performance of conventional and superabrasive grinding wheels
Keywords: Alumina; CBN; Resin bond; VC 131 steel; Abrasives; Cutting fluids; Grinding (machining); Steel; Strength of materials; Surface roughness; Superabrasives; Grinding wheels